Effect of Cash Flow and Corporate Social Responsibility Disclosure on Firm Value - Jannati Tangngisalu (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study examines and analyzes the effect of cash flow and corporate social responsibility disclosure on firm value. The main difference between this study and previous research is that cash flow and corporate social responsibility are collectively used as the class's independent variables with the dependent variable firm value. This research uses quantitative methods with an associative form. The research population is all banking companies listed on the Indonesia Stock Exchange for the period 2017-2019. The sample using a purposive sampling technique so that 33 companies were selected according to the sample determination criteria with a sample size of 99 examples analyzed using the multiple regression analysis models. The results showed that the cash flow variable had a positive and significant effect on firm value and corporate social responsibility disclosure also had a positive impact on firm value. This implies that investors see how flexible the company's cash flow can be used to finance the company's operational activities and increase investment, which impacts improving the welfare of shareholders. Corporate social responsibility disclosure shows that sustainability signals and increased corporate prosperity depend on the economic dimension and depend on social and environmental dimensions.